Corrosion Inhibition of Mild Steel in 2M HCl Using Aqueous Extract of Eggplant Peel - Ibrahim, Taleb (2011)
The objective of this study was to investigate the inhibitive action of eggplant peel extract toward the corrosion of mild steel in 2M HCl solution by employing weight loss measurements and electrochemical techniques. The results of both methods showed that the corrosion rate is decreasing and inhibition efficiency is increasing as the concentration of the eggplant inhibitor increased. The adsorption data were analyzed using various adsorption isotherm models and the results at temperatures of 25, 40 and 50°C have shown that the adsorption behavior of eggplant extract molecules is best described by the Langmuir adsorption isotherm.